REFORMASI PENDIDIKAN ISLAM DI INDONESIA - Muh. Idris (Marwah: Jurnal Perempuan, Agama dan Jender, 2013)
Education reform aims to be effective and efficient in achieving national education goals. In Laws and Regulations seen the desire of the Indonesian government to empower the people of Indonesia through the provision of superior education. The government clearly has put content standards, processes, competence of graduates, educators and education personnel, facilities and infrastructure,management, finance, and educational assessment.Over a period of more than five decades since Indonesia is free fromcolonialism, Islamic education can be said to have not been able to contribute anything to the progress of the nation, in addition to not being able to complain when required role in addressing the problems of this nation’s morals and mentality. Islamic education and Islamic boarding school either unwittingly still stuck on dichotomous orientation. The indication, the Islamic educational institutions is the transformation of knowledge and religious values was so strong that it is almost forgotten reality of the labor market.